Eksperimen Biolistrik pada Tanaman untuk Mengembangkan Sumber Energi Alternatif Berbasis Hayati - Andi Arlina; Andi Syarifah Irmadani (CV. Aksara Global Akademia, 2024)
This study explores the potential of water hyacinth (Eichhornia crassipes) as a bioelectricity source through Plant-Microbial Fuel Cell (PMFC) technology. The research aimed to evaluate the ability of water hyacinth to generate stable electrical energy when integrated with electrodes in a controlled laboratory setting. The method applied was an experimental laboratory design, where water hyacinths were placed in containers filled with water, equipped with anode and cathode electrodes, and connected to a voltmeter and ammeter for continuous monitoring. Observations were carried out for 72 hours with periodic recording of voltage and current values. The findings show that water hyacinth can generate measurable electricity, with voltage ranging from 0.25 V to 0.32 V and current between 0.18 mA and 0.24 mA, indicating the potential of this plant to produce renewable energy. Moreover, the results reveal that the generated electricity was relatively stable during the observation period, though variations occurred due to environmental conditions. The implications of this research suggest that water hyacinth, often considered a weed, can be utilized not only for energy production but also as part of ecological management programs. This dual function makes PMFC technology a promising alternative for sustainable energy development, especially in rural or remote areas where access to conventional electricity remains limited.